Association Between Race and Length of Stay Among Stroke Patients: The National US Emergency Departments Data Set - Karan Patel; Kamil Taneja; Jared Wolfe; Joseph V. Campellone; Mudassir Farooqui; Santiago Ortega‐Gutierrez; James E. Siegler (Stroke: Vascular and Interventional Neurology, 2023)
Background There remain ongoing racial and ethnic disparities in care and outcomes among stroke patients treated in the United States. However, length of stay and inpatient charges warrant further evaluation. Methods The 2019 Nationwide Emergency Department Sample, which includes data from roughly 20% of US emergency departments, was queried for patients with cerebral infarction. Multivariable logistic regression was used to estimate the odds of prolonged length of hospital stay (>75th percentile) and inpatient charges among various race andethnic groups, including income and insurance status, age, modified Charlson Comorbidity Index, vascular risk factors, and delivery of thrombolysis and thrombectomy. Results Of 617 946 estimated patients with acute ischemic stroke, 398 661 (65.5%) were >65 years, and 386 096 (63.5%) were Medicare beneficiaries. Lower income and Medicaid or self‐pay status were more commonly observed in Black and Hispanic versus White patients (P<0.001). In multivariable regression, Black patients were more likely to have a prolonged length of stay (odds ratio 1.41, [95% CI 1.28–1.55]) compared with White patients. Prolonged length of stay was inversely related to income, but there was no significant interaction between race and income bracket (P>0.05). Prolonged length of stay was also associated with Medicaid (versus Medicare), higher modified Charlson Comorbidity Index, thrombolysis, and thrombectomy (P<0.05). Race was not independently associated with higher inpatient charges. Conclusion These results build on prior population‐based studies that indicate ongoing disparities in stroke care based on differences in socioeconomic status and race, but no difference in inpatient charges. Disposition delays may be due to clinical severity or access to rehabilitation facilities.